169 Examining the relationship between app usage and injury prevention behavior change. (5th May 2020) - Omaki, Elise; Shields, Wendy; McDonald, Eileen; Aitken, Mary; Gielen, Andrea
Abstract : Purpose: Safety in Seconds (SIS) is a smartphone app that has demonstrated effectiveness at changing injury prevention behaviors. The aim of this analysis was to understand how parents engaged with each component of the app and determine if there was an association between app usage and behaviors. Methods: Parents of children aged 4–7 visiting the pediatric emergency room in the two participating sites (regardless of the reason for the visit) were recruited. Study participants downloaded the SIS app onto their smartphone and were randomized receive car seat or fire safety information. Both groups completed a 10-minute assessment about their safety knowledge and behaviors and received tailored feedback relevant to their study group. The app contained a portal with educational links and sent monthly push notification reminders for parents to interact with the app. Parents completed follow-up assessments at 3- months and 6-months. Results: Among the 602 parents completing all follow up points, 37% visited each page of the report, 19% emailed the report to themselves or someone else, and 33% visited the Parent Portal. Among 555 parents reporting at least one unsafe behavior at baseline, 130 (23.5%) changed their safety behaviors and reported no unsafe behaviors at the 6-month follow up. Those changing their behavior had more mean clicks (24 vs. 18; p<0.0001), were more likely to have visited all pages of the report (48% vs. 32%; p<0.01) and emailed the report (29% vs. 15%; p<0.001) than those who did not change their behavior. In a multivariable logistic regression, those visiting all pages of the report (OR 1.58; 95% CI 1.00, 2.50) or emailing the report (OR 1.77; 95% CI 1.07, 2.94) were more likely to have changed their behavior at six months than those not. Conclusion: Smartphone applications hold potential for changing behaviors that are known to improve child passenger safety.